Respostas

2014-05-21T22:46:13-03:00
Considerarei x² + 10x + 16=0 

delta = 10² - 4.1.16 
delta = 100 - 64 
delta = 36 

x' = (-10 + √36)/2 
x' = (-10 + 6)/2 
x' = -4/2 = -2 

x'' = (-10 - √36)/2 
x'' = (-10 - 6)/2 
x'' = -16/2 = - 8 

x' = -2 
x'' = -8
A melhor resposta!
2014-05-21T23:05:55-03:00
X² -10x +16=0
a= 1  b= -10  c=16
Δ= b² -4.a.c
Δ= (-10)² -4 .1 .16
Δ= 100 -64
Δ=36
x= \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(-10)+- \sqrt{36} }{2.1}
x'= \frac{10+6}{2}
x'= \frac{16}{2}
x´=8
x''= \frac{10-6}{2}
x''= \frac{4}{2}
x''=2
1 5 1
coloca na calculadora e veja o resultado
tendii Rs
kkk
eu esqeço desses detalhes
isso acontece